Levels of Some Blood Clotting Factors in COVID-19 Patients: Comparative Study Before and After Pfizer- BioNTech Vaccinations - Al-Assaf, Lubna A.A.; Al-Issa, Yasser A.H. (Iraqi Journal of Science, 2023)
One of the health issues that a coronavirus can induce is blood clotting. Coronavirus can be prevented in a number of ways. Vaccination is one of the critical methods for preventing illness or lessening its impact. This study seeks to estimate a few blood coagulation variables. 147 samples were collected from the Baghdad Governorate in the autumn of 2021. The samples were split into three groups: COVID-19 patients, healthy individuals before and after receiving the (Pfizer-BioNTech) vaccine, and healthy individuals only. Prothrombin Time (PT), Partial Thromboplastin Time (PTT), Protein C (PTN-C), Protein S (PTN-S), and International Normalized Ratio (INR) for 49 samples were measured and computed for each group. The results have shown that the PTN-C and PTN-S concentrations were significantly decreased in the COVID-19 patients compared to unvaccinated healthy individuals. While INR of COVID-19 patients showed a highly significant increase when compared with unvaccinated healthy individuals. At the same time, there was no significant difference for each PT and PTT between these studied groups. The parameters exhibit identical findings when COVID-19 patients are compared to those who have had vaccinations, with the exception of PT, which reveals a highly significant rise in COVID-19 patients when compared to those who have received vaccinations. Conclusion: COVID-19 causes blood clots and may be recognized by a decrease in PTN-C and PTN-S content.